Pyogenic Granuloma of External Auditory Canal: A Case Report - Karki, Utsav R; Dongol, Kripa; Pradhananga, Rabindra B; Shah, Bikash K (Journal of Institute of Medicine Nepal, 2023)
The external auditory canal is an atypical location for Pyogenic Granuloma (PG) to originate. We report a case of PG in a 15-year-old boy's external auditory canal. He experienced reduced hearing and occasional blood-tinged ear discharge for 8 months. Examination revealed a pinkish-soft mass occluding the canal lumen. Pure tone audiogram showed 42 dB moderate conductive hearing loss in the right ear. High-resolution computed tomography showed a well-defined, homogenously enhancing soft tissue density lesion in the canal. The mass was completely excised, and post-operative histopathology confirmed the diagnosis of PG. No recurrence was observed during the six-month follow-up period. PG should be considered in the differential diagnosis of external auditory canal lesions.